2011
DOI: 10.1371/journal.pntd.0001449
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Production Depends on IL-12 and IL-18 Combined Action and Mediates Host Resistance to Dengue Virus Infection in a Nitric Oxide-Dependent Manner

Abstract: Dengue is a mosquito-borne disease caused by one of four serotypes of Dengue virus (DENV-1–4). Severe dengue infection in humans is characterized by thrombocytopenia, increased vascular permeability, hemorrhage and shock. However, there is little information about host response to DENV infection. Here, mechanisms accounting for IFN-γ production and effector function during dengue disease were investigated in a murine model of DENV-2 infection. IFN-γ expression was greatly increased after infection of mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 58 publications
4
71
1
Order By: Relevance
“…However, the interpretation of these data is limited by the fact that no information on its natural antagonist IL-18BP is given as well. The same applies to the in vitro and animal studies that also suggested an important role for IL-18 in the pathogenesis of dengue virus (7)(8)(9). In the present study, we document high plasma IL-18 levels concurring with increased IL- tumor necrosis factor alpha (TNF-␣) (C), IL-6 (D), and IL-1 receptor antagonist (IL-1Ra) (E) in Indonesian adults with dengue fever (n ϭ 95) during the febrile (n ϭ 14), critical (n ϭ 77), early recovery (n ϭ 72), and convalescence (n ϭ 54) phases; with leptospirosis (n ϭ 19); and with enteric fever (n ϭ 6) and in a control group of healthy adult Indonesians (n ϭ 22).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the interpretation of these data is limited by the fact that no information on its natural antagonist IL-18BP is given as well. The same applies to the in vitro and animal studies that also suggested an important role for IL-18 in the pathogenesis of dengue virus (7)(8)(9). In the present study, we document high plasma IL-18 levels concurring with increased IL- tumor necrosis factor alpha (TNF-␣) (C), IL-6 (D), and IL-1 receptor antagonist (IL-1Ra) (E) in Indonesian adults with dengue fever (n ϭ 95) during the febrile (n ϭ 14), critical (n ϭ 77), early recovery (n ϭ 72), and convalescence (n ϭ 54) phases; with leptospirosis (n ϭ 19); and with enteric fever (n ϭ 6) and in a control group of healthy adult Indonesians (n ϭ 22).…”
Section: Discussionmentioning
confidence: 81%
“…IL-18, together with IL-12, plays a major role in the production of gamma interferon (IFN-␥). This was also shown in a murine dengue model, in which IL-18 acted in synergism with IL-12 to induce IFN-␥ and other T-helper 1 cytokines, which are considered central mediators in dengue host defense (8,9).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Because an increased capacity to mount cytotoxic responses toward DVinfected target cells was associated with a decreased likelihood of developing severe dengue disease (7), the ability of IL-18 to enhance the cytotoxic responses of gd T cells against DV-infected targets might be an important determinant of dengue disease severity. Further studies will be required to address this possibility, particularly because it is unclear whether IL-18 plays a protective role during dengue infection (47) or is associated with adverse outcomes (43).…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 appears to cooperate or act synergistically with IL-18 in the control of intracellular parasite infection of macrophages (7) or bridging innate and adaptive immunity (8)(9)(10). Notably, treatment of differentiated macrophages with IL-12/ IL-18 but not with M-CSF induces the production of IFN-g (5,6,11).…”
mentioning
confidence: 99%